1997
DOI: 10.1016/s0029-7844(97)00299-8
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of Platelet Activation Throughout Normal Gestation

Abstract: Pregnancy does not increase the percentage of activated platelets in the circulation. Platelet reactivity is altered in the third trimester, as evidenced by decreased antibody binding to fibrinogen receptor epitope and enhanced down-regulation of a von Willebrand factor receptor epitope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In addition, Janes and Goodall 7 , reported significantly higher h-thromboglobulin per platelet, while Gerbasi et al 6 , showed significant increases in h-thromboglobulin and platelet factor 4 in normal pregnant women compared with non-pregnant controls. However, in contrast, Romero et al 8 found no significant difference in plasma h-thromboglobulin concentrations between nonpregnant controls and pregnant women, and studies by Gatti et al 9 and Star et al 26 , using flow cytometry, reported no significant effect of pregnancy on platelet activation. Initially, it was proposed that, owing to the rapid loss of surface P-selectin from circulating degranulated platelets, increases in platelet activation were not observed in the studies using flow cytometric methodology 11 , and consequently, Ferroni et al 27 concluded that sP-selectin was a more reliable marker of in vivo platelet activation.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, Janes and Goodall 7 , reported significantly higher h-thromboglobulin per platelet, while Gerbasi et al 6 , showed significant increases in h-thromboglobulin and platelet factor 4 in normal pregnant women compared with non-pregnant controls. However, in contrast, Romero et al 8 found no significant difference in plasma h-thromboglobulin concentrations between nonpregnant controls and pregnant women, and studies by Gatti et al 9 and Star et al 26 , using flow cytometry, reported no significant effect of pregnancy on platelet activation. Initially, it was proposed that, owing to the rapid loss of surface P-selectin from circulating degranulated platelets, increases in platelet activation were not observed in the studies using flow cytometric methodology 11 , and consequently, Ferroni et al 27 concluded that sP-selectin was a more reliable marker of in vivo platelet activation.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, Janes and Goodall 7 , reported significantly higher β‐thromboglobulin per platelet, while Gerbasi et al 6 , showed significant increases in β‐thromboglobulin and platelet factor 4 in normal pregnant women compared with non‐pregnant controls. However, in contrast, Romero et al 8 found no significant difference in plasma β‐thromboglobulin concentrations between non‐pregnant controls and pregnant women, and studies by Gatti et al 9 and Star et al 26 , using flow cytometry, reported no significant effect of pregnancy on platelet activation. Initially, it was proposed that, owing to the rapid loss of surface P‐selectin from circulating degranulated platelets, increases in platelet activation were not observed in the studies using flow cytometric methodology 11 , and consequently, Ferroni et al 27 concluded that sP‐selectin was a more reliable marker of in vivo platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence that platelet lifespan is decreased or that platelet activation occurs in normal pregnancy [13,14]. Thus, the decrease in platelet counts appears to occur from hemodilution as well as platelet trapping.…”
Section: Introductionmentioning
confidence: 99%